PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN HIJAB ZOYA (Studi pada konsumen Hijab Zoya di Zoya Semarang Jl. Kaligarang No. 9B) - Amik Mariana, 15.05.51.0101; Soliha, Euis (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of Product Quality, Brand Image and Price Perception on the Purchase Decision of Hijab Zoya (Study on consumers of Hijab Zoya in Zoya Semarang Jl. Kaligarang No. 9B). This study also aims to jointly determine the effect of the three independent variables on the dependent variable and to find out which variables are the most dominant influence among the three independent variables on the dependent variable. This type of research uses quantitative research data, with a population of one hundred Zoya hijab consumers. Data collection uses a questionnaire with a Likert scale. Based on the calculation of SPSS 21 from the t test on product quality variables, brand image and price perception all variables are accepted. The F Test results show variable product quality, brand image, and price perception show simultaneously together in the purchasing decision.